Literature Studies: The Use of Technology as a Media for Learning Arabic in the Digital Era - Gita Putri Ramadhani; Mad Ali (Journal of Practice Learning and Educational Development, 2025)
The rapid advancement of digital technology today has had a significant impact on various aspects of life, including education. In the field of language learning, particularly Arabic, technology has introduced innovations that open new opportunities to enhance the quality and efficiency of the teaching and learning process. With digital technology, the integration of interactive media, online learning platforms, mobile applications, and artificial intelligence can create a more engaging, flexible, and personalized learning experience. This study aims to identify the types of technology that have been applied in Arabic language learning. A qualitative method with a literature review approach was employed in this research. The data sources were drawn from journals discussing relevant themes on the use of technology as a medium for teaching Arabic. The data were then analyzed to generate new findings. The analysis revealed 21 technology-based learning media that effectively support Arabic language learning, including Instagram, TikTok, Google Sites, Moodle, Duolingo, YouTube, Animated Films, Plotagon, Powtoon, Kahoot, Digital Comics, Quizizz, Chatbot Mondly, Canva, Adobe Animate CC, Podcasts, MixPad, Word Wall, Digital Dictionaries, BISA Nahwu Sharaf Application, and Alef Education Platform. These media contribute to enhancing students' listening, speaking, reading, and writing skills. These findings are expected to serve as strategic references for educators and educational institutions to develop more innovative and relevant Arabic language learning approaches in the digital era.